The micro-structural characterization of thermosonic cu-al intermetallic compounds and modelling of its interface stress - Chua, Kok Yau (2015)
Thermosonic bonding of the Cu wire on Al bond pad is a common technology used in semiconductor industry. However, recent research show voids formation at this bonding interface on micro-chip, after an annealing treatment of High Temperature Storage (HTS). This voids formation is believed due to the volumetric changes of intermetallic compounds (IMCs) formed at the bonding interface. In previous research, effects of Cu free-air-ball and bonding temperature with high temperature storage (HTS) treatment on Cu-Al bonding interface are unclear. Besides, previous research provides inconclusive knowledge in the evolution of Cu-Al bonding interface due to inconsistent observations and variations in the bonding parameters. Research with statistical approach could be useful to address this limitation, however, it is yet to be established for Thermosonic Cu-Al interconnection. Besides, the void formation due to volumetric changes of IMC is discussed only qualitatively. A quantitative stress analysis could close the gap of research. Objectives of this research are (1) to analyse the correlation of wire bonding parameters, the interfacial micro-structure change and mechanical strength of the synthesized Cu-Al bonding interface, (2) to propose a theoretical model that describe quantitatively the stress due to volumetric changes originated from Cu-Al phase evolution, (3) to evaluate the stress generated by Cu-Al phase evolution at the bonding interface and its correlation to the void formation. Micro-structural characterizations were focused on crystallographic, compositional and mechanical analyses. It was found that bonding temperature resulted in an exponential increment for initial overall IMC thickness and average Cu content of the phases formed at the bonding interface. Moreover, HTS increase the overall IMC thickness by volume diffusion mechanism. The relationship between parameters, mechanical ball shear strength and IMC thickness were obtained statistically. A mathematical stress model based on assumptions of isotropic and elastic binary solid-solution was proposed. This model enabled an estimation of interfacial stresses from compositional measurements. It was found that the stress developed by interfacial Cu-Al IMC generally increased with the bonding temperature. Besides, forming gas supply was found to be less significant to affect the stress development, due to the oxide layers did not hinder much the interdiffusion of Cu and Al atoms. However, with HTS, the growth of Cu rich IMC increased the stress and caused gap within copper oxide layer. This work addressed the research gaps and offered a better understanding of the fundamental of Thermosonic Cu-Al interconnection. The results of the stress modelling could be a useful failure analysis technique for implementing Cu wire in the industry.